Collection / Whitney Museum of American Art - Whitney Museum of American Art (2015)
[Dt.:] Das Whitney Museum of American Art in New York beherbergt eine der wichtigsten Sammlungen zeitgenössischer amerikanischer Kunst des 20. Jahrhunderts. Über die Online-Collection sind die Bestände zugänglich. - [Engl.:] The Whitney's collection online provides unprecedented access to works by more than 3,000 artists. These works in all mediums - painting, sculpture, drawing, printmaking, photography, film, video, installation, and new media - serve as a remarkable resource for understanding art history and the creative process of artists in the United States from 1900 to today.